ELECTROCHEMICAL BEHAVIOR OF TELLURIUM IN ACIDIC NITRATE SOLUTIONS (Metallurgy and Foundry Engineering, 2014)
Electrochemistry of tellurium stationary electrode was studied in acidic nitrate solutions with pH 1.5 – 3.0. Cyclic voltammetry indicated that two products were formed at potentials above 300 mV (SCE): soluble HTeO2+ (500 mV) and sparingly soluble H2TeO3 (650 mV), but the former seemed to be an intermediate product for TeO2 precipitation on the electrode surface. Formation of the solid products as porous layers was almost undisturbed and no electrode passivation was observed. H2TeO3 and TeO2 dissolved to HTeO2+ under acidic electrolyte, but this process was hindered by pH increase. Cathodic polarization of tellurium electrode below -800 mV was accompanied by evolution of H2Te, which was then oxidized at the potentials approx. -700 mV. H2Te generated in the electrochemical reaction decomposed to elemental tellurium as black powdery precipitates in the bulk of the solution and a bright film drifting on the electrolyte surface.